Impacts of COVID-19 on the Life and Work of Healthcare Workers During the Nationwide Partial Lockdown in Vietnam - Pham, Quan Thi; Le, Xuan Thi Thanh; Phan, Tam Chi; Nguyen, Quang Nhat; Ta, Nhung Kim Thi; Nguyen, Anh Ngoc; Nguyen, Thao Thanh; Nguyen, Quynh Thi; Le, Huong Thi; Luong, Anh Mai; Koh, David; Hoang, Men Thi; et al. (Frontiers in Psychology, 2021)
Background: Healthcare workers are front-line responders facing a disproportionate increase in occupational responsibilities during the COVID-19 pandemic. Added work-related stress among healthcare personnel may lead to personal and work-related repercussions, such as burn-out or decreased quality of care for patients. However, little is known about how the COVID-19 pandemic affects their daily work and life. This study aimed to evaluate the personal and occupational impacts among hospital staff during the partial lockdown in Vietnam because of COVID-19. Methods: A cross-sectional web-based study was carried out to collect respondents’ demographic data and personal and job impacts during the second week of national lockdown in April 2020. Snowball sampling technique was applied to recruit 742 hospital staff. The exploratory factor analysis (EFA) was used to examine the validity of the instrument. Results: Of the 742 respondents, 21.2% agreed that “working attitude well maintained” followed by 16.1% of respondents reported that there were “enough employees at work.” Only 3.2% of respondents agreed that “their work was appreciated by society” Healthcare workers in the central region were less likely to have experienced "Avoidance of disclosure and discrimination related to COVID 19" than other areas (Coef. = -0.25, CI: -0.42 to -0.07). Being female has a negative association with scores in “Avoidance of disclosure and discrimination related to COVID 19” domain (Coef. = -0.27, CI: -0.43 to -0.12) while having a positive association with “Negative attitude towards working conditions” domain (Coef. = 0.19, CI:0.09 to 0.3). Healthcare workers working in administrative offices (Coef. = 0.20; 95% CI = 0.05 to 0.36) and infectious departments (Coef. = 0.36; 95% CI = 0.09 to 0.63) had positive association with "Increased work pressure due to COVID 19” domain. Conclusion:Our findings revealed marginal impacts of the COVID-19 pandemic on the work and life of hospital staff in Vietnam. Moreover, this study highlighted the importance of implementing preventive strategies during the nationwide partial lockdown to manage hospital admissions and a burden on healthcare workers. This study finally characterizes targeted demographics that may benefit from appreciation by employers and society during a national pandemic.